Albania : Second and Third Reviews Under the Extended Arrangement and Request for Waiver for the Nonobservance of Performance Criterion, Waiver of Applicability of Performance Criteria, and Rephasing of Future Disbursements. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Albania's Second and Third Reviews Under the Extended Arrangement and Request for Waiver for the Nonobservance of Performance Criterion, Waiver of Applicability of PCs, and Rephasing of Future Disbursements. The program is on track. All end-June, end-September, and available end-December quantitative PCs were met. However, the continuous PC on the accumulation of external arrears was not observed because of technical delay with one interest payment. The IMF staff supports the authorities' request for the completion of the second and third reviews under the Extended Arrangement, waiver of applicability of PCs, and rephasing of future disbursements.